Edukasi Literasi Keuangan dan Investasi di Pasar Modal bagi Generasi Muda - Anisah, Nur; Prasetyo, Deni Widyo (Transpublika Publisher, 2024)
The primary goal of this community service initiative is to educate the local community, specifically the younger demographic, on ways to enhance the village's economy by promoting financial literacy and encouraging investment in the stock market. The approach utilised in these community service endeavours involves mentoring and interactive discussions. As a result of these activities, the young residents of Pandan Blolele Village in Ploso District and Bangsri Village in Plandaan District, Jombang Regency have been successfully introduced to and have implemented financial literacy and investment concepts from the stock market into their daily lives. By equipping them with this knowledge, they are less likely to fall victim to deceitful investments or unreliable digital financial platforms that operate outside the regulations of the Financial Services Authority (OJK) when they eventually become active members of society. The results of this mentoring provide a positive contribution in collaboration with youth organizations, schools, village community empowerment and universities.